Rare Medico Legal Cases of Pediatric Intensive Care Unit - KILIÇ, Serbülent; OTO, Arzu (Ahi Evran Medical Journal, Kirsehir Ahi Evran University, 2023)
Objective: Although the MLCs who are admitted to the Pediatric Intensive Care Unit establish a crucial health burden, the risk factors, epidemiologic data and clinical signs of such cases have not been documented in a regular and comprehensive way. Methods: A retrospective patient review was made. This study was conducted in the PICU of Bursa Yuksek Ihtisas Training and Research Hospital, Bursa, Turkey, between 01 January 2017 and 01 January 2022. This study enrolled 31 males (35.4%) and 17 females (64.6%) aged 4.7 ±4.1 years. We classified MLCs into nine groups as Foreign Body Aspiration (FBA), Blunt Trauma (BT), Asphyxia (ASP), Firearm Injury (FI), Sharp and Penetrating Object Injury (SPOI), Electric Injury (EI), Sports-Related Injury (SRI), Animal Bite Injury (ABI), Home Accident (HA). Results: FBA is the dominant type of MCL of this study (29,1%). The average hospital stay of FBA cases in the ward was 3 (1-11) days; in PICU was 2 (1-8) days. The average hospital stay of BT cases in the ward was 4 (1-12) days; in PICU was 3 (1-10) days. The average hospital stay of ASP cases in the ward was 2 (1-6) days; in PICU was 2 (1-7) days. 29,1 percent of the patients (n=14) required the surgery. In our study, we calculated that the mean voice of treatment of a case is 5744 ₺ (around US$308,57). The most significant proportion of the MLCs was caused by FBA (n=14, 43%), followed by BT (n=9, 18%) and ASP (n=8, 16%). Conclusion: All parties which want to make decrease in the number of the MLCs, should draw attention to prevention efforts
Keywords: 3. Good health